Dufour and Soret effects on Al2O3-water nanofluid flow over a moving thin needle: Tiwari and Das model. Issue 3 (1st July 2020) - Waini, Iskandar; Ishak, Anuar; Pop, Ioan
Abstract : Purpose: This paper aims to examine the effect of Dufour and Soret diffusions on Al2 O3 -water nanofluid flow over a moving thin needle by using the Tiwari and Das model. Design/methodology/approach: The governing equations are reduced to the similarity equations using similarity transformations. The resulting equations are programmed in Matlab software through the bvp4c solver to obtain their solutions. The features of the skin friction, heat transfer and mass transfer coefficients, as well as the velocity, temperature and concentration profiles for different values of the physical parameters, are analysed and discussed. Findings: The non-uniqueness of the solutions is observed for a certain range of the physical parameters. The authors also notice that the bifurcation of the solutions occurs in which the needle moves toward the origin (λ < 0). It is discovered that the first branch solutions of the skin friction coefficient and the heat transfer coefficients increase, but the mass transfer coefficient decreases in the presence of nanoparticle. Additionally, the simultaneous effect of Dufour and Soret diffusions tends to enhance the heat transfer coefficient; however, dual behaviours are observed for the mass transfer coefficient. Further analysis shows that between the two solutions, only one of them is stable and thus physically reliable in the long run. Originality/value: The problem of Al2 O3 -water nanofluid flow over a moving thin needle with Dufour and Soret effects are the important originality of the present study. Besides, the temporal stability of the dual solutions is examined for time.